Greater chance of high core temperatures with modified pacing strategy during team sport in the heat - Aughey, R. J.; Goodman, C. A.; McKenna, M. J. (Journal of Science and Medicine in Sport, 2014)
Objectives: To measure the activity profile, hydration status and core temperature of elite team sport athletes during matches in hot and cool conditions.